Design of Air-Jet Assisted Vertical Rotation Natural Fiber Opener - MOHD DARUS, NORLIYANA; Shaari, Muhammad Farid (Progress in Engineering Application and Technology, 2024)
Banana pseudo-stem fibers have great potential to be developed into high value fibers that can be produced into yarns and felts. Loose raw fiber is prepared by extracting the fibers from banana pseudo-stem and breaking it into loose fibers. The current method of fiber breaking process utilizes horizontal spiked drums technique. It has challenges such as fibers are being cut too short, irregular fiber orientation and inconsistent opening. With Air-jet Assisted Vertical Rotation Natural Fiber Opener design, it can improve fiber alignment and uniformity which can improve the separation and produce finer fibers. In this study, the method used is by taking fiber weight samples before and after the opening process at a predetermined minute rate which is the first, fifth and tenth minutes and then make a comparison. Two fiber weights have been set which are 30g and 60g. As a result, the fiber opener design works well in the fiber opening process and the fibers are opened more finely and cleanly from contaminants with the help of air jets. The combination of air jets and vertical rotation design contributes to the effectiveness of the opening mechanism, making it a valuable tool for various applications in the textile industry.